In-Law Interference and Emotional Stability of Married Women in Kwara State, Nigeria (Journal of Guidance and Counselling Studies, 2025)
Emotional stability of married women is a complex and multifaceted phenomenon, is influenced by numerous factors, including domestic violence. This research investigated In-law interference and emotional stability of married women in Kwara State, Nigeria. At 0.05 level of significance, one research question was postulated and three null hypotheses were tested.  The study employed a descriptive survey of correlational type. A total of 403 married women were selected from nine out of sixteen local government in Kwara State took part in the study. A researcher-designed questionnaire titled “In-law Interference and Emotional Stability Questionnaire (IIES)” was the instrument used to collect data from the respondents. The data collected was analyzed using descriptive and inferential statistics. Demographic factors such as years in marriage, education,  religion, and number of children influenced both interference and stability. The findings show that in-law interference could lead to stress, marital dissatifaction, and emotional instability in a marriage. Counselling interventions were recommended to help couples set healthy boundaries and improve communication in order to achieve effectiveness and a wholesome marriage.